DS3 Model testing. Assessing critical infrastructure network flood resilience at the neighbourhood scale. - Serre, Damien (Springer, 2018)
The behaviour of the urban network infrastructures, and their interactions during flood events, will have direct and indirect consequences on the flood risk level built environment. By urban network infrastructures we include all the urban technical networks like transportation, energy, water supply, waste water, telecommunications... able to spread the flood risk in cities, qualified as critical infrastructures due to their major roles for modern living standards. From history, of cities in the world have been built close to coast lines or to river to beneficiate this means of communication and trade. Step by step, to avoid being flooded, defences like levees have been built. The capacity of the levees to retain floods depends on their conditions, their performance level and the capacity of the authorities to well maintain these infrastructures. But recent history shows the of a flood risk management strategy focused on protection, leading to levee breaks these last twenty years, for example in the South of France. Then, in case of leeve break, cities will be flooded. The urban technical networks, due to the way they have been designed, their conditions and their locations in the city, will play a major role in the diffusion of the flood extent. Also, the flood risk will have consequences in some not flooded neighbourhoods due to networks collapses and complex interdependencies. This chapter describes some methods to design spatial decision support systems in that context.
Keywords: Hochwasser; Überschwemmung; Überflutung; Städtische Infrastruktur; Kritische Infrastruktur; Hochwasserschutz; Risikomanagement; Verwaltungshandeln; Entscheidungsfindung; Modell; Fallbeispiel